2023
DOI: 10.1186/s12870-023-04530-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics integrated with metabolomics reveals the effect of cold stress on rice microspores

Yingbo Li,
Yingjie Zong,
Wenrui Li
et al.

Abstract: Background Microspore culture is one of the important biotechnological tools in plant breeding. The induction of microspore embryogenesis is a critical factor that affects the yield of microspore-derived embryo productions. Cold treatment has been reported to reprogram the gametophytic pathway in various plant species. However, the exact mechanism(s) underlying the effect of cold pre-treatment of floral buds on the efficiency of ME is still not clear. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For example, by integrating transcriptomic and metabolomic approaches, researchers have revealed the importance of specific genes in regulating the phenylpropane pathway in response to cold stress. Gu et al demonstrated the crucial role of the OsSEH1 gene in this process [71], while Li et al elucidated the mechanism of cold stress in rice pollen, providing a theoretical basis for guidance for inducing callus formation in rice pollen [72]. Arsenic (As) is a carcinogen, and its accumulation in rice can lead to growth restriction.…”
Section: Functional Gene Mining By Multi-omicsmentioning
confidence: 99%
“…For example, by integrating transcriptomic and metabolomic approaches, researchers have revealed the importance of specific genes in regulating the phenylpropane pathway in response to cold stress. Gu et al demonstrated the crucial role of the OsSEH1 gene in this process [71], while Li et al elucidated the mechanism of cold stress in rice pollen, providing a theoretical basis for guidance for inducing callus formation in rice pollen [72]. Arsenic (As) is a carcinogen, and its accumulation in rice can lead to growth restriction.…”
Section: Functional Gene Mining By Multi-omicsmentioning
confidence: 99%
“…Genes that were differentially expressed had to have an FPKM value of at least 10 and a false discovery rate (FDR) of at least 0.05. Kyoto Encyclopedia of the Genome (KEGG) and Gene Ontology (GO) enrichment were used for functional analysis [32].…”
Section: Rna Extraction Library Construction Rna Sequencing and Data ...mentioning
confidence: 99%
“…As this experiment included three biological replicates, analysis of variance was conducted using the DESeq2 software package (version 1.30.1). DEGs were identified based on a significant p-value < 0.05 and |log2 fold change| > 1 [40]. Heatmaps illustrating gene expression levels and Venn diagrams displaying DEGs were generated using TB tools software (version 1.120).…”
Section: The Analysis Of Degsmentioning
confidence: 99%